2010
DOI: 10.1021/es100967z
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Measurements of NO3Radical at a Semiarid Urban Site: 2. Seasonal Trends and Loss Mechanisms

Abstract: This study is the first to present long-term measurements of the nitrate radical in an urban location. Extensive nitrate radical measurements were conducted together with ancillary parameters during a continuous two year campaign (2005-2007) in the semiarid location of Jerusalem. The average nighttime NO3 concentration was 27.3+/-43.5 ppt, the highest ever reported, with a seasonal average peak during summer (33.3+/-55.8 pptv) with maximum levels exceeding 800 pptv. Significant diurnal changes in NO3 concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 30 publications
(62 reference statements)
4
47
1
Order By: Relevance
“…The relatively high OH concentrations during haze days in winter in Beijing could accelerate oxidation of gas species and further promote formation of secondary particles. The NO 3 concentrations were calculated to be in the range from 2.82 × 10 9 to 4.86 × 10 9 molecules cm −3 on clear days, which were in good agreement with the maximal value (4.92 × 10 9 molecules cm −3 ) reported in Houston during winter (Asaf et al, 2010). It should be mentioned that the OH and NO 3 derived from the propane / propene ratios could only represent their lower limits because of the continued mixing of fresh emissions with the aged air.…”
Section: Diurnal Variations In Propane / Propene Ratiossupporting
confidence: 81%
“…The relatively high OH concentrations during haze days in winter in Beijing could accelerate oxidation of gas species and further promote formation of secondary particles. The NO 3 concentrations were calculated to be in the range from 2.82 × 10 9 to 4.86 × 10 9 molecules cm −3 on clear days, which were in good agreement with the maximal value (4.92 × 10 9 molecules cm −3 ) reported in Houston during winter (Asaf et al, 2010). It should be mentioned that the OH and NO 3 derived from the propane / propene ratios could only represent their lower limits because of the continued mixing of fresh emissions with the aged air.…”
Section: Diurnal Variations In Propane / Propene Ratiossupporting
confidence: 81%
“…A limitation of our estimates of areal mass is that they were standardized to the top 0−40 cm soil depth and do not account for potentially different soil depths; this may not be a major issue given that most Hg is considered to accumulate in surface reservoirs. 7,28 Spatial patterns of atmospheric Hg concentrations and rates of depositionfor example, as assessed by the EPA Toxics Release Inventory for Hg, 50 Hg wet deposition based on National Atmospheric Deposition Program maps, 51 and atmospheric gaseous and oxidized Hg levels and depositions based on models 17 are not known to show latitudinal gradients and, hence, are unlikely to directly cause these south−north gradients. Climate gradients can affect mean residence times of C in soils and terrestrial ecosystems, 52 and this may be linked to observed latitudinal gradients of THg and MeHg concentrations and areal mass.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…One of the dominant NO 3 loss pathways during the day and at the surface at night is the reaction with NO (Wayne et al 1991;Asaf et al 2010):…”
Section: Indirect Loss Pathwaysmentioning
confidence: 99%